(untitled) - Mehmet Rasin Tek (New York)
This book gives state-of-the-art methods and technology for inventory verification, delivery assurance, and salt cavity storage. It provides a comprehensive review and discussion of the current technology as well as new developments for the inventory and delivery of natural gas
Keywords: natural gas - underground storage